PENGARUH PARAMETER PEMESINAN TERHADAP KEKASARAN PERMUKAAN AI6061BE PADA PEMESINAN CNC MINI 500 WATT MENGGUNAKAN PAHAT KARBIDA STRAIGHT ENDMILL - Napitupulu, Richard A. M.; Perangin angin, Siwan E.A. (Jurnal Rekayasa Mesin, 2024)
The role of automatic machining with the help of computer programming such as Computer Numerically Controlled (CNC) has become commonplace today in both large and small industrial sectors or micro industry. CNC is a manufacturing process where previously programmed computer software is converted into code that can automate machining movements, one of which is the milling or lathe process. CNC performance is determined by machining output power. For micro industrial or laboratory scale, CNC with low power is usually used to cut soft materials such as wood, acrylic, aluminum and others. This is the basis for this research to look at the influence of machining parameters such as speed, depth of cut and feed rate on the surface roughness (Ra) of AI6061BE aluminum workpieces in the dry machining process on a mini CNC unit with a maximum spindle power of 500 watts. This research uses an experimental design based on the Taguchi method and takes the form of an L16 (43)  orthogonal matrix. The chisel used is a Straight End Mill 2 fluke carbide chisel. The experiment was carried out 4 times cutting in the positive x-axis direction and 4 times in the negative x-axis direction for each variation of machining parameters. From the test results, surface roughness, feed rate is a parameter that is more influential than speed and depth of cut.